A Correlational Study on The Financial Management Practices and Financial Reporting Quality Among Retail Businesses - Precious Zyra A. Almadin; Abegel R. Soriano; John Mark V. Mira; Eligen H. Sumicad Jr.; Mylene P. Alfanta (AKTIVA: Journal of Accountancy and Management, 2026)
Research Purpose: This study examined the relationship between financial management practices and the financial reporting quality of retail businesses in Pagadian City. It focused on how financial planning, investment decisions, and working capital management relate to relevance, faithful representation, comparability, verifiability, understandability, and timeliness. The aim was to determine whether structured financial management improves the reliability and transparency of reports among SMEs.Method or Approach: The study used a quantitative descriptive-correlational design. A standardized survey questionnaire was administered to 105 managers of small and medium retail businesses selected through consecutive sampling. The instrument measured three financial management dimensions and six reporting-quality attributes using a 4-point Likert scale. Data were analyzed using descriptive statistics and Pearson correlation in SPSS.Research Findings: Financial management practices were rated “Very High” (mean = 3.46), with working capital management scoring highest. Financial reporting quality was also “Very High” (mean = 3.35), with timeliness ranking highest. Spearman correlation showed a significant high positive relationship between the variables (r = .589, p < .05), indicating that stronger financial management contributes to more accurate, timely, and reliable reports.Recommendations or Novelty: This study offers new empirical evidence from Pagadian City, where research on this topic is limited. Drawing on Agency Theory, it shows how effective financial management reduces information asymmetry and enhances reporting quality. Its contribution lies in jointly assessing financial management dimensions and reporting-quality characteristics, providing insights for policymakers, educators, and business owners seeking to strengthen transparency among retail SMEs. Tujuan penelitian: Penelitian ini mengkaji hubungan antara praktik manajemen keuangan dan kualitas pelaporan keuangan pada bisnis ritel di Kota Pagadian. Fokus penelitian mencakup bagaimana perencanaan keuangan, keputusan investasi, dan manajemen modal kerja berkaitan dengan relevansi, representasi setia, keterbandingan, keterverifikasian, keterpahaman, dan ketepatan waktu. Tujuannya adalah menentukan apakah manajemen keuangan yang terstruktur meningkatkan keandalan dan transparansi laporan pada usaha kecil dan menengah.Metode atau pendekatan: Penelitian menggunakan desain kuantitatif deskriptif-korelasional. Kuesioner standar diberikan kepada 105 manajer usaha ritel kecil dan menengah yang dipilih melalui consecutive sampling. Instrumen mengukur tiga dimensi manajemen keuangan dan enam atribut kualitas pelaporan menggunakan skala Likert 4 poin. Data dianalisis menggunakan statistik deskriptif dan korelasi Pearson melalui SPSS.Temuan penelitian: Praktik manajemen keuangan dinilai “Sangat Tinggi” (mean = 3,46), dengan manajemen modal kerja memperoleh skor tertinggi. Kualitas pelaporan keuangan juga “Sangat Tinggi” (mean = 3,35), dengan ketepatan waktu sebagai indikator tertinggi. Korelasi Spearman menunjukkan hubungan positif yang tinggi dan signifikan antara variabel (r = 0,589; p < 0,05), yang mengindikasikan bahwa manajemen keuangan yang lebih kuat berkontribusi pada laporan yang lebih akurat, tepat waktu, dan andal. Kontribusi atau Kebaruan: Penelitian ini memberikan bukti empiris baru dari Kota Pagadian, di mana studi mengenai topik ini masih terbatas. Dengan menggunakan Teori Keagenan, penelitian menunjukkan bagaimana manajemen keuangan yang efektif mengurangi asimetri informasi dan meningkatkan kualitas pelaporan. Kontribusinya terletak pada penilaian terpadu antara dimensi manajemen keuangan dan karakteristik kualitas pelaporan, memberikan wawasan bagi pembuat kebijakan, pendidik, dan pemilik usaha untuk memperkuat transparansi pada UKM ritel.